CURRENT STATE OF THE ICHTHYOFAUNA OF THE KAZAKH PART OF THE AKSU RIVER (SHU RIVER BASIN, KAZAKHSTAN) (Experimental biology, 2025)
The study of the ichthyofauna of transboundary rivers plays a key role in the conservation of ecosystems, sustainable management of fish resources, and restoration of their populations. These studies help to develop effective measures for the protection of fish species, prevent their depletion, and ensure the harmonious coexistence of ecosystems and human activities. The article presents such information as the main hydrochemical characteristics of the Kazakh part of the Aksu River, the diversity of its ichthyofauna, the frequency of occurrence of species in different areas, diversity indices, and similarity indices. According to ichthyological studies conducted in 2023-2024, the taxonomic composition of the Aksu River was 9 species. Of these, 3 species are native, 6 are alien. Native species:  roach Rutilus lacustris (Pallas, 1814), freshwater bream Abramis brama orientalis Berg, 1949, turkestan gudgeon Gobio lepidolaemus (Kessler 1872). Alien species: stone moroko Pseudorasbora parva (Temminck et Schlegel, 1846), prussian carp ...
Keywords: Aksu River; fish communities; similarity; alien species; transboundary river